ASSESSMENT OF PRESCRIPTION WRITING SKILLSAND ERRORS AMONGST DENTAL HOUSE SURGEONS AND FACULTY MEMBERS (Baqai Journal of Health Sciences)
Objective:The study aimed to assess knowledge and prescription writing skills among faculty members and especially the house officers regarding each prescription writing parameter. Method: A total of 101 participants were part of the studywho filled the forms with consent. However,the main focus of the study was the house officers in particular. The study was conducted at Baqai Dental College. A questionnaire was designed to assess the prescription writing skills. Results: Most of the participants (62.4%) attendeda course on how to prescribe medicines. A significant number of participants (79.2%) had good knowledge and awareness about the properties of the medicines they were prescribing. Conclusion: The current study concluded that the knowledge and prescription writing skills of the majority of house surgeons were adequate in many vital details and skills